On homotopy nilpotency - Golasiński, Marek (Array, 2021)
We review established and recent results on the homotopy nilpotence of spaces. In particular, the homotopy nilpotency of the loop spaces Ω(G/K) of homogenous spaces G/K for a compact Lie group G and its closed homotopy nilpotent subgroup K